ANALISIS PENERAPAN KEGIATAN EKSTRAKURIKULER STEAM PADA ANAK USIA 5-6 TAHUN DI TK KARYA YOSEF PONTIANAK KOTA - Kristina Yanti; Diam Miranda; Ariyani Ramadhani (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this study is to analyze the implementation of each component in the STEAM extracurricular activities for children aged 5-6 years at TK Karya Yosef Pontianak Kota. The research employed a qualitative method with a descriptive approach. The data source for this study was one STEAM extracurricular mentor at TK Karya Yosef Pontianak Kota. Data collection tools included observation sheets, interview guidelines, and documentation. The results of the study revealed that: (1) The science component is implemented through various activities, such as introducing concepts, conducting experiments, observing, identifying problems, communicating, and drawing conclusions. (2) The use of technology is adapted to the activities and abilities of the children. At the initial stage, the technology used is simpler and safer. (3) The engineering process is consistently applied in every STEAM extracurricular activity, where children actively participate in project creation and engage in analyzing and solving problems. (4) The art component is implemented using simple materials, such as food coloring, paint, and origami paper. (5) The mathematics component is carried out through activities such as counting and measuring.